Trade and Religion in British-Benin Relations, 1553-1897 - Aremu, Johnson Olaosebikan; Ediagbonya, Michael (Global Journal of Social Sciences Studies, 2018)
This work examines the British-Benin relations anchored largely on trade and religion between 1553 and1897. The study documents extensively the features and impact of trade on Benin Kingdom’s relations with Britain during the period of study. It further analyses the attendant re-invigoration of Christianity in Benin land by the British in the late 18th century; the cordiality of Benin-British relations and the unexpected British invasion of Benin in 1897 which led to the sudden collapse of the Benin Kingdom. The work relied on both oral interviews and documentary data as primary sources. The secondary sources consist of relevant books, newspapers publications, journal articles, theses, and dissertations. The study found that Benin-British relations started in the sixteenth century. It also found that the relationship was facilitated by trade and religion. It was also found that the C.M.S and Roman Catholic established schools which promoted education in Benin. Finally, it was observed that, in spite of the healthy trade relations between both countries, the relationship finally ended with the British invasion of Benin in 1897.